Graffiti as Social Narratives: A Thematic Analysis of Student Expression at Jagannath University - Sagar Chandra Nath (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
This study analyzes thematic structure of the graffiti painted on the walls of Jagannath University campus, Dhaka to explore the attitudes of contemporary student community. It considers graffiti not as mere aesthetic works, but as visible documents which record contemporary experience of Bangladeshi students. The study follows a qualitative method and reads the language, symbols and images of graffiti through direct observation, collection of 160 photographs and thematic analysis. The analysis shows that structural issues such as administrative criticism, democratic rights and insecurity have emerged strongly in the campus graffiti. At the same time, the quota reform movement, the July mass uprising of Bangladesh, international solidarity, religious, leftist and feminist consciousness and the demand for the rights of indigenous peoples are visible through graffiti. Along with these political statements, personal feelings such as love, loneliness, economic tensions and the search for self-identity have also found a place on the walls, which highlights the psychological reality of the students. The study shows that one of the main themes in the graffiti of Jagannath University is the various adverse conditions of the university students. This graffiti is identified as an important research area in understanding student politics and social movements. It is possible to enrich the knowledge in this field by conducting more extensive research in the future.